Challenges and opportunities for atomic physics at FAIR: the new GSI accelerator project - Hagmann, Siegbert; Kluge, Heinz-Jürgen (Nuclear instruments & methods in physics research. Section B, Beam interactions with materials and atoms, 2005)
We present a short overview of the current status of the new accelerator project FAIR at GSI with the new double synchrotron rings and the multi-storage rings. The key features of the new facility, which provides intense relativistic beams of stable and unstable nuclei, are introduced and their relation to the anticipated experimental programs in nuclear structure physics and antiproton physics is shown. The main emphasis in this overview is given to the atomic physics program with unique opportunities which will be provided e.g. by bare U92+ ions with kinetic energies continuously variable between relativistic energies corresponding to γ up to ≅35 down to kinetic energies of such ions in traps corresponding to fractions of a Kelvin.